2021
DOI: 10.1007/s40974-021-00215-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact assessment on water quality in the polluted stretch using a cluster analysis during pre- and COVID-19 lockdown of Tawi river basin, Jammu, North India: an environment resiliency

Abstract: Pollution-free rivers give indication of a healthy ecosystem. The stretch of Tawi river particularly in the Jammu city is experiencing pollution load and the quality is degraded. The present study highlights the impact of COVID-19 lockdown on the water quality of Tawi river in Jammu, J&K Union Territory. Water quality data based upon the real-time water monitoring for four locations (Below Tawi Bridge, Bhagwati Nagar, Belicharana and Surajpur) have been obtained from the web link of Jammu and Kashmir Pollution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…On the other hand, recent development activities in the basin are threatening the river's water quality [6,23,52] and may jeopardize its ability to meet water demands. Furthermore, pollution from industries, manufacturers, commercial organizations, and animal farms along the river has the potential to worsen the degradation of water quality [53].…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the other hand, recent development activities in the basin are threatening the river's water quality [6,23,52] and may jeopardize its ability to meet water demands. Furthermore, pollution from industries, manufacturers, commercial organizations, and animal farms along the river has the potential to worsen the degradation of water quality [53].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies reported that the environmental conditions at various parts of globe increased in terms of reduced air and water pollution ( Braga et al, 2020 ; Chauhan and Singh, 2020 ; Collivignarelli et al, 2020 ; Dantas et al, 2020 ; Lal et al, 2020 ; Li et al, 2020 ; Muhammad et al, 2020a , Muhammad et al, 2020b ; Otmani et al, 2020 ; Chakraborty et al, 2021 ; Najahe t al., 2021 ; Tokatlı and Varol, 2021 ). In India also studies shows that both air quality and water quality across the country improved during lockdown period ( Thomas et al, 2020 ; Chauhan and Singh 2020 ; Saadat et al, 2020 ; Yunus et al, 2020 : Aman et al, 2020 ; Kulk et al, 2021 ; Chakraborty et al, 2021 ; Kour et al, 2021 ). To study whether the reduction in anthropogenic activities during the nationwide lockdown led to improved water quality in Asthamudi Lake, Southern India, the present study used multi-spectral remote sensing observations to analyses changes in the SPM as a water quality indicator.…”
Section: Introductionmentioning
confidence: 99%
“…It is the single river to complete the requirement of water in Jammu city where more than 10 million people are directly dependent on its water. [5][6][7]…”
Section: Introductionmentioning
confidence: 99%